Gadyatrayam of Begavat [i.e. Bhagavad] Ramanujacharya: text in Sanskrit with the commentary of Sri Periavachan Pillai - Periyavāccāṉapiḷḷai ca. 15. Jh. (Sri Rangapriya Pathippakam, 2002)
Gadyatrayam, collection of Rāmānuja's three prose pieces (Śaraṇāgati gadyaṃ, Śrīranga gadyaṃ, and Vaīkuṇṭha gadyam), contain the essences of teachings